The Study of Learning Theory in terms of Motor Skills - Suci Mutia Lukman; Neviyarni Neviyarni (Indonesian Institute for Counseling, Education and Theraphy, 2021)
This article discusses motor skills, which can be interpreted as movement skills of a person from the learning results they get, many motor skills are innate, the learning of motor skills has played a big role in human history. Learning motor skills (motor skill learning) refers to all activities in which the learning process requires a sequence of motor responses (body movements). Learning motor skills refers to all activities in which the learning process requires a sequence of body motor responses (motor responses) appropriately. The term perceptual motor skills is used to describe the fact that this type of learning requires coordinating stimuli that are consistent with motor responses. Learning motorskills is a learning process that uses perceptuals and processes them into motoricactions, where learning activities are a sequential process of sensing activitiesthat are then applied with skills.